Drug transporters: molecular characterization and role in drug disposition - You, Guofeng; Morris, Marilyn Emily (Wiley-Interscience, 2007)
A comprehensive guide to drug transporters that influence the absorption, distribution, and elimination of drugs in the body. The development of powerful expression cloning and genome analysis techniques has facilitated the molecular identification and characterization of numerous transporters that play a crucial role in drug disposition. Explaining the principles of drug transport and the associated techniques, Drug Transporters: Molecular Characterization and Role in Drug Disposition:.:. ;. Provides a comprehensive overview of drug transporters. ;. Includes specific descriptions of transport
Includes bibliographical references and index
Keywords: Arzneistoffträger; Pharmakokinetik; Wirkstoff-Rezeptor-Bindung; Stofftransport; Arzneimittel